Rancang Bangun Miniatur Alat Perontok Sorgum - Budriyadi, Syefi; Nata, Yudi (Universitas Nusa Putra, 2020)
The purpose of this research is to make it easier for farmers to harvest sorghum and avoid crop failure due to lack of supporting technology to produce ready-to-sell sorghum seeds. The method used in the process of designing the machine with the engineering process, namely the activity of designing a sorghum thresher machine, a miniature sorghum thresher machine was successfully designed with the main components: Hopper, threshing unit, threshing room, driving motor, frame, seed outlet and sorghum panicle. And with a machine capacity capable of threshing 10kg/hour sorghum seeds with a rotation speed of 2800rpm.